Design of Stunting Information System to Improve Employee Performance of Pertumbukan Village Office, Wampu District - Kurniawan, Fahmi; Sitorus, Zulham; Rian Putra, Randi; Afrizal, Sandi (Bahasa Indonesia, 2024)
Along with current technological developments, the application of information systems in a government agency is needed, because the rapid development of technology requires an agency to use information system technology in supporting performance in data processing to obtain faster and more accurate information, one of which is stunting data processing. This study aims to evaluate how the implementation of the stunting information system can improve the performance of village office employees to support the government to reduce the number of stunting in Pertumbukan Village, Wampu District. The method used is qualitative with data collection techniques through interviews, observations, and documentation studies. The results showed that the implementation of the stunting information system provided a number of benefits for village office staff such as improved performance, operational efficiency, and better ability to share stunting data information. In addition, the stunting information system also makes it easier for village office staff to manage data, monitor stunting residents, and make decisions for prevention and treatment. However, there are challenges such as lack of stunting literacy and limited infrastructure. With proper training and central government support, Pertumbukan Village Office employees in Wampu Sub-district are expected to be able to optimally utilize the stunting information system to improve performance in stunting data processing